2015
DOI: 10.1007/s40336-015-0121-3
|View full text |Cite|
|
Sign up to set email alerts
|

Role of intraoperative sentinel node imaging in head and neck cancer

Abstract: At the present time, there is a dilemma concerning the best management of the neck in patients presenting with early head and neck squamous cell carcinoma (HNSCC). Occult cervical metastasis is found in up to a quarter of HNSCC patients with radiologically N0 necks, and for this reason, conventional treatment includes elective neck dissection (END) alongside tumour excision. Sentinel node biopsy (SNB) offers an alternative accurate and minimally invasive method of staging the neck, which has been safely applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It is tempting to offer frail patients SNB to avoid risks associated with END. However, 20%‐30% of patients will have a positive SNB (SNB+) and will require staged completion (therapeutic) neck dissection (CND). Frail patients who have undergone SNB can sometimes deteriorate after initial surgery and may not recover sufficiently to undergo CND.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is tempting to offer frail patients SNB to avoid risks associated with END. However, 20%‐30% of patients will have a positive SNB (SNB+) and will require staged completion (therapeutic) neck dissection (CND). Frail patients who have undergone SNB can sometimes deteriorate after initial surgery and may not recover sufficiently to undergo CND.…”
Section: Recommendationsmentioning
confidence: 99%
“…A number of studies have confirmed that 2‐3 sentinel nodes normally are removed per patient. Occasionally just one sentinel node is identified; rarely more than five are encountered, usually in patients with bilateral drainage . It is appreciated that the economic advantage of SNB is reduced when multiple nodes are sent for serial sectioning.…”
Section: Recommendationsmentioning
confidence: 99%